Effects of soil and fault properties on tunnel displacement induced by normal and reverse faults - Ghafari, Mehdi (2020)
As the world population increasing considerably in tandem with the growing cities, economies, and businesses, there is a need for effective and efficient public transportation. One of the fastest, and most convenient public transport is subway. However, it has become a major concern to geotechnical engineers as the development and construction of subways are held underground where faults exist. Several seismic events such as the earthquakes in Taiwan in 1999, China in 2008, and Malaysia (Sabah) in 2015 caused by fault ruptures signify the importance of this study. Although many studies have been conducted on fault ruptures, most researchers only considered a free field (a field without tunnels) and on homogeneous cohesionless soil (sand). In this study, a gigantic physical model 1000 mm in height, 3000 mm in length, and 1000 mm in width was fabricated in Geotechnical Engineering laboratory, Universiti Putra Malaysia (UPM) to evaluate the influence of various soil properties on tunnels affected by both normal and reverse faults, as well as the effects of various fault angles and tunnel depths. Three different soil cohesion have been selected, cohesionless soil , 10 kPa and 20 kPa which due to the reason that cohesionless soil has been used in most of previous studies, and other studies (in soil stability), cohesion values of less than 23 kPa has been used. Three different soil friction angles have been investigated in this study, 27°, 33° and 39°. Previous studies have showed that range of soil friction angle between 28° and 39° indicated density of up to 80%. Results revealed that increasing the soil cohesion and friction angle resulted in reducing tunnel displacements by as much as 64% and 39% respectively. Investigation on the differences and similarities between normal and reverse faults revealed that reverse faults can bring approximately 60% more tunnel displacements compared to normal faults because a normal fault released less energy than a reverse fault. Another aspect considered is the influence of fault angles in which results showed that vertical movements due to a fault angle of 90° could bring major displacements of more than two times the displacements caused by a fault angle of 30°. Evaluation of the effects of various distances between a tunnel and a fault revealed that tunnel displacements could be reduced by more than 22% when the tunnel is located 250 mm away from the fault. In addition, finite element analyses were also performed using PLAXIS to simulate and compare the results with physical model. The results of the current study could be of benefit to society considering the fault ruptures. Many metropolitan cities with underground structures are exposed to risks to many lives if fault ruptures occurred. This study asserts that besides the structural design of a tunnel, the geotechnical design also has a major impact on the safety and robustness of the tunnel. It is also shown that geotechnical engineering aspects such as soil properties, type of fault, tunnel depth, and fault angle have a strong influence on tunnel damages in which those aspects were not considered in previous research despite their importance.